KORELASI HASIL BELAJAR MAHASISWA PADA MATA KULIAH STRUKTUR HEWAN DENGAN PERKEMBANGAN HEWAN DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UR 2012/2013 - Arnetis '; Evi Suryawati; Selfia Fitri Anggriani (Program Studi Pendidikan Biologi, 2013)
The purpose of this study was to determine the correlation of Student Learning Outcomes between Animal Structure and an Animal Development subject conducted in Biology Education in Guidance and Counseling the University of Riau in March-June 2013. This research is a descriptive correlational study. The sample was 50 students from biology class of 2010 by using purposive sampling technique. Parameter data of the study are student learning outcomes in animal structure and animal development subject consisting of the average score of task, the average score of quiz, Mid-term score (UTS), the score of the final-term (UAS). The instruments of data collection such as secondary data are using data documentation of student learning outcomes include average score of task, quiz average value, the mid-term score and the final-term score calculated by the formula of product moment correlation and primary data obtained through closed questionnaire as supporting data. The results showed that the difference of correlation index, it could be seen at the 5% significance level of the correlation coefficient on the average score of the task is weak (0.22), the coefficient of the correlation on the average score of quiz was classified as very weak (0.05), the coefficient of correlation on the mid-term score (UTS) has a sufficient correlation (0.52), the coefficient of correlation on the final-term score (UAS) has a sufficient correlation (0.55) and the coefficient of correlation on the total value has a strong correlation (0,64). It can be concluded that there is a positive and significant correlation with the total value of the animal structure and animal development subject (0,64).Keywords: Animal Development, Animal Structure, Correlation.